2018
DOI: 10.5487/tr.2018.34.1.041
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Antiretroviral Therapy Alters Sperm Parameters and Testicular Antioxidant Status in Diet-Induced Obese Rats

Abstract: The efficacy of highly active antiretroviral therapy (HAART) has led to an increase demand for therapeutic use, thereby necessitating investigation into drug toxicity. This study was designed to investigate the in vivo effects of HAART on sperm parameters and testicular oxidative stress in lean and obese rats. Wistar rats (males, n = 40, weighing 180~200 g) were assigned randomly into 4 groups and treated accordingly for 16 weeks as follows: Control (C): lean group fed with standard rat chow; Diet induced obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 41 publications
5
26
0
Order By: Relevance
“…Nevirapine and Efavirenz have been shown to cross the blood-brain barrier and cause significant inhibition in the activity of creatine kinase, which plays a vital role in imparting cell energy homeostasis in the brain [28]. Generally, one of the theories propounded to explain antiretroviral drug toxicities partly involves mitochondria oxidative stress induction [19,29], causing accelerated aging and lifespan reduction [30].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevirapine and Efavirenz have been shown to cross the blood-brain barrier and cause significant inhibition in the activity of creatine kinase, which plays a vital role in imparting cell energy homeostasis in the brain [28]. Generally, one of the theories propounded to explain antiretroviral drug toxicities partly involves mitochondria oxidative stress induction [19,29], causing accelerated aging and lifespan reduction [30].…”
Section: Discussionmentioning
confidence: 99%
“…Some in vitro studies have shown the relationship between acetylcholine and fecundity [19,29]. Generally, the higher the activity of AChE, the lower the concentration of acetylcholine (ACh).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spermatozoa were retrieved from murine (Wistar and Sprague-Dawley rats (Rattus norvegicus) and C57 strain mice (Mus musculus)) and non-murine (naked mole-rat (Heterocephalus glaber)) animals postmortem after the animals had been humanely killed with a lethal dose of sodium pentobarbital, halothane or cervical dislocation. The testis and epididymis were subsequently removed and spermatozoa were harvested from the proximal cauda epididymis using a sperm isolation procedure as described by Maree (2011) for mouse and naked mole-rat and by Oyeyipo et al (2018) for rat.…”
Section: Laboratory Rodentsmentioning
confidence: 99%